KEEFEKTIFAN KONSELING KELOMPOK ADLER UNTUK MENINGKATKAN KETERAMPILAN INTERPERSONAL SISWA SMP - Fitriani, Mega Rahma; Hidayah, Nur (Jurnal Kajian Bimbingan dan Konseling, 2016)
Interpersonal skills is one of the skills that must be owned by a person in a relationship with other people. A person who failed in developing their interpersonal skills will be found difficulty in many aspects their life, especially on their social aspects. The purpose of this study is to know the effectiveness of Adler group counseling for improving interpersonal skills of junior high school students. This type of study is an quasi experimental method and program of study interrupted time series. From the result of hypotheses which is using wilcoxon signed ranks test, it is concluded if Adler group counseling affective to improving interpersonal skills of junior high school students.